VD_FINDINFO Arrêt / 2012 / 123 vom 19. März 2012 - VD Tribunal cantonal (2012)
RENTE D'INVALIDITÉ, PRIORITÉ DE LA RÉADAPTATION, ÉVALUATION DE L'INVALIDITÉ | 28 LAI, 29 al. 1 LAI, 4 al. 1 LAI, 16 LPGA, 7 LPGA, 8 LPGA